BARRIERS TO EXPORT FROM INDIA TO THE EUROPEAN UNION - Chaudhari, Mangal Bhausaheb; Giedraitis, Vincent; Kapse, Pankaj (Ekonomika, 2012)
India is an important trade partner for the European Union. The European Union’s export to India is higher relative to India’s export to the European Union. An analysis of barriers is needed for international trade as it may assist in finding out why exporters are not able to exploit their full potential. The main goal of this research is to analyze the barriers faced by Indian exporters during export to the European Union. This research was done by an empirical investigation of barriers’ perception by Indian exporters. A literature review was also done to enlist the barriers faced by exporters. Analysis of data was done with the help of SPSS (Version 20) software.While previous researches talk about the most common barriers, this research talks about all the possible ones, i.e. common as well as naturally existing, and finds the major ones. This research has shown that exporters have a significant feeling for governmental regulations, customs procedure and licensing, technical standards and health regulations, sanitary and phytosanitary measures, and certification as the major barriers to export. There are some naturally existing barriers to the trade among which labeling and packaging, and market access problems are the major barriers to export.Decreasing the strength of these barriers will lead to an increase in export as exporters are ready to export more from India to the European Union if these barriers will be removed or the strength of these barriers will be less. Also, due to the low barriers, non-exporters will start export, and the increase in export will lead to the economic growth of India.